The DIVERSIFIKASI PRODUK DAN PERHITUNGAN HARGA POKOK PRODUKSI KOPI - Sulaiman Sarmo; Sri Darwini; Imanuella Romaputri Andilolo (Buletin SWIMP, 2021)
This coffee business is located in Pagutan Permai and was founded in 2015. This submersible coffee manager only produces natural coffee and calculates production costs based on the cost that costs money, in addition to marketing with less attractive packaging and marketing network more to the closest family. Therefore, we as a service team need to provide counseling assistance and product diversification training and calculation of the cost of production as well as how to market using technology and design attractive packaging for customers. This training will be carried out for 4 months by providing counseling and training as well as identifying problems, while in calculating the cost of goods using a full-cost approach, and marketing models using Instagram. The results of the dedication of the coffee business actors are very responsive to this activity, and try to diversify ginger coffee and soy coffee products, as well as create a coffee product brand with the name KOHEJA, and market it via Instagram